Хороший динозавр: [перевод с английского] (Золотая классика Disney, 2015)
Экземпляры: ф.17 (20230519) / Инвентарный номер: 63611 / Цена: / Сис.шифр: 84(7Coe)-4 / Авт.знак: Х 82 / ГРНТИ: 17.82.93 / ББК: 84(7Coe)-4